Decrease in the Antioxidant Capacity in Beverages Containing Tea Extracts during Storage. (10th September 2012) - Nekvapil, Tomas; Kopriva, Vladimir; Boudny, Vladimir; Hostovsky, Martin; Dvorak, Petr; Malota, Ladislav
Abstract : The aim of this work was to determine antioxidant capacity of beverages containing black, white, and green tea extracts using the photochemiluminescence method, and to monitor its changes based on the storage temperature and time. Samples were stored at two different temperatures (refrigerated at 4°C and laboratory temperature 22°C), analyzed after opening of the original package, and consequently after 4 and 7 days. Results of the antioxidant capacity are expressed as the standard equivalents, that is, ascorbic acid in mmol/L. The highest mean value of the antioxidant capacity was found after opening of the original package in fruit-juice-enriched samples and totaled 9.793 mmol/L. This group revealed significant dependence (P < 0.05 ) not only on the storage time, but also temperature. In samples without added fruit juices containing preservatives the value was 0.428 mmol/L. This group showed significant dependence (P < 0.05 ) on the decrease of antioxidant capacity only when based on the storage time. Samples without fruit juices or preservatives showed significant decrease in the antioxidant capacity (P < 0.05 ) after 4 days of storage based on the storage time. The dependence on temperature was revealed only after 7 days of storage.